Behavioral disorders identification, assessment, and instruction of students with EBD - Bakken, Jeffrey P.; Obiakor, Festus E.; Rotatori, Anthony F. (Bingley, U.K. : Emerald, 2012)
The area of behavioral disorders is constantly changing and advancing as a result of legislation, new trends, and current research investigations.Currently, there is no comprehensive resource that effectively covers these advances with the breath of topics as this volume. Though it is difficult to keep up with all issues and trends, this volume presents critical topics in all spheres of this area of study.
Preface / Jeffrey P. Bakken, Festus E. Obiakor, Anthony F. Rotatori -- ch. 1. Legal issues and teachers of students with emotional and behavioral disorders / Mitchell L. Yell, Shelley L. Neilsen Gatti -- ch. 2. Themes and dimensions of emotional and behavioral disorders / April L. Mustian, Yojanna Cuenca-Sanchez -- ch. 3. Assessment of students with emotional and behavioral disorders / Cynthia A. Plotts -- ch. 4. Placement of students with emotional and behavioral disorders / Sarup R. Mathur, Kristine Jolivette -- ch. 5. Placement of culturally and linguistically diverse students in programs for students with emotional and behavioral disorders : contemporary trends and research needs / Alfredo J. Artiles, Aydin Bal, Stanley C. Trent, Kathleen King Thorius -- ch. 6. Prevention of and early intervention for students with emotional and behavioral disorders : systems to support data-based decision making / Timothy J. Lewis, Barbara S. Mitchell -- ch. 7. English language learners and emotional behavioral disorders / Diana L. Rogers-Adkinson, Theresa A. Ochoa, Stacy L. Weiss -- ch. 8. Behavior modification/traditional techniques for students with emotional and behavioral disorders / Paul Mooney, Joseph B. Ryan, Philip L. Gunter, R. Kenton Denny -- ch. 9. Differentiated instruction for students with emotional and behavioral disorders / Christy Borders, Stacey Jones Bock, Nichelle Michalak -- ch. 10. Hobson's choice : illusory intervention choice for culturally and linguistically diverse learners with problem behaviors / Festus E. Obiakor.
Keywords: Education -- Special Education -- Learning Disabilities; Education -- Special Education -- General; Teaching of specific groups & persons with special educational needs; Teaching of students with emotional & behavioural difficulties; Special education; Behavior disorders in children; Behavior disorders in adolescence